The Frequency of Risk Factors For Coronary Heart Disease Among Women Aged 35 Years or Over In The Yenimahalle Health Center Region In Elazığ - Açık, Yasemin; Oğuzöncül, Ferdane; Pirinçci, Edibe; Güngör, Leyla (Fırat University, 2001)
The objective of this study was to determine the frequency of risk factors for coronary heart disease among women aged 35 years or over in the Yenimahalle Health Center region in Elazığ. In this research, 340 of 6213 women living in health center region, were chosen by randomly. 332 of them (97.6%) were reached by repetition meetings. 64.4% of researched women were illiterate. Average age of them was 49.74±10.33. 13.2% of them were current smoker. Women's average; diastolic blood pressure, systolic blood pressure, body mass index and cholesterol level were 79.04±12.99, 126.89±22.82, 29.73±5.21 and 197.07±42.55 respectively. Women indicated that 11.1% of them were diabetic. 34.6% of them had an hypertension. 8.1% of them had an heart disease. 3.3% of heart disease was coronary heart disease. This study shows that the prevalence of risk factors for coronary heart disease was high among women aged 35 years or over in this region. Thus, it is advisable that primary health care services for the general population should also consider the prevention of coronary heart disease as a priority.

Yenimahalle Eğitim Araştırma Sağlık Ocağı bölgesinde yaşayan 35 yaş ve üstü kadınlarda koroner kalp hastalığı risk faktörleri sıklığını saptamak amacıyla yapılan bu çalışmada; sağlık ocağı bölgesinde yaşayan 6213 kadının 340'ı randomize sayılar cetvelinden yararlanılarak seçilmiş, tekrarlayan ziyaretlerle 332'sine (%97.6'sı) ulaşılmıştır. Her sağlık evi nüfus büyüklüğüne göre örneklemde temsil edilmiştir. Çalışmaya alınan kadınların %64.4'ü herhangi bir okul mezunu değildir. Ortalama yaşları 49.74 ±10.33'dir. %13.2'si halen sigara içmektedir. Kadınların ortalama; diyastolik kan basınçları 79.04±12.99, sistolik kan basınçları 126.89± 22.82, Vücut kitle indeksi 29.73±5.21, kolesterol düzeyi 197.07± 42.55'tir. Kadınların %11.1'i kendisinde daha önceden doktor tarafından tanısı konmuş şeker hastalığı, %34.6'sı hipertansiyon, %8.1'i ise kalp hastalığı olduğunu bildirmiştir. Kalp hastalıklarının %3.3'ü koroner kalp hastalıklarıdır. 35 yaş ve üzeri kadınlarda koroner kalp hastalığı risk faktörleri görülme sıklığı oldukça yüksektir. Temel sağlık hizmeti sunumu içinde yaşam tarzı değişikliği önerilerini de içeren eğitim ve hizmet sunumuna öncelik verilmelidir.
YENİMAHALLE EĞİTİM ARAŞTIRMA SAĞLIK OCAĞI BÖLGESİNDE YAŞAYAN 35 YAŞ VE ÜSTÜ KADINLARDA KORONER KALP HASTALIĞI RİSK FAKTÖRLERİ SIKLIĞI